2018
DOI: 10.15644/asc52/4/10
|View full text |Cite
|
Sign up to set email alerts
|

Oral Manifestation as the Main Sign of an Advanced Stage Acute Promyelocytic Leukemia

Abstract: Acute myeloid leukemia is an aggressive malignant neoplasm occurring mainly in elderly, with the median age of 65 years. Oral manifestations, mainly spontaneous bleeding, are a common finding in acute myelocytic leukemia and may represent the initial evidence of the disease. This report describes a case of a 47-year-old man with a one-month history of spontaneous oral bleeding. The patient had already been consulted by two professionals but he remained undiagnosed. The physical examination revealed paleness, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The oral MOLs were in gingival tissue (63.63%), 9 , 12 , 17 , 18 , 19 , 21 , 23 , 24 , 25 , 26 , 27 , 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 15 , 40 alveolar and jugal mucosa (18.18%) 14 , 18 , 21 , 22 , 26 , 28 and hard or soft palate (18.18%). 9 , 11 , 15 , 16 , 27 , 30 Other regions, such as the floor of the mouth (12.12%), 13 , 16 , 23 , 38 tongue (9.09%), 13 , 33 , 39 lip (3.03%), 13 parotid glands (3.03%), 10 and nasolabial region (3.03%), 26 were less frequent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral MOLs were in gingival tissue (63.63%), 9 , 12 , 17 , 18 , 19 , 21 , 23 , 24 , 25 , 26 , 27 , 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 15 , 40 alveolar and jugal mucosa (18.18%) 14 , 18 , 21 , 22 , 26 , 28 and hard or soft palate (18.18%). 9 , 11 , 15 , 16 , 27 , 30 Other regions, such as the floor of the mouth (12.12%), 13 , 16 , 23 , 38 tongue (9.09%), 13 , 33 , 39 lip (3.03%), 13 parotid glands (3.03%), 10 and nasolabial region (3.03%), 26 were less frequent.…”
Section: Resultsmentioning
confidence: 99%
“…The blood count was the main blood test requested to help support the presumptive diagnosis of an oral MOL. Thrombocytopenia was present in 22 cases (59.09%), 9 , 10 , 24 , 25 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 12 , 39 , 40 , 14 , 15 , 17 , 18 , 21 , 22 , 23 anemia was present in 23 cases (63.63%), 9 , 10 , 25 , 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 12 , 39 , 40 , 14 , 15 , 17 , 20 , 22 , 23 , 24 leukocytosis was present in 19 cases (45.45%) 9 , 11 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 13 , 15 , 17 , 18 ,…”
Section: Resultsmentioning
confidence: 99%
“…Although oral manifestations are not rare, these are usually gingival enlargement and bleeding, oral ulcers, petechiae, and mucosal pallor. 3 These occurrences are either following direct infiltration of the leukemic cells or secondary to the impaired function of the hematopoietic cells. A recently published review article by Quispe et al 4 concluded that oral cavity can harbor the initial manifestations of leukemia, particularly acute myeloid leukemia (AML).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, over 30% of individuals who are diagnosed with leukemia experience various oral manifestations [ 12 ]. The most commonly observed findings include gingival hypertrophy, spontaneous bleeding, petechiae, ulcerations, and oral mucosa pallor [ 11 , 13 ]. The initial indications of leukemia often become apparent in the oral cavity as a result of the invasion of leukemic cells in oral tissues or the reduction of normal bone marrow elements (red cells, white blood cells, and platelets), particularly during the acute stage of the illness [ 14 ].…”
Section: Introductionmentioning
confidence: 99%